Zum Beitrag „Einige Interpolationsaufgabe in der Klasse H_δ, δ < 1“ - Kabaila, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Кабайла. К статье «Некоторые задачи интерполяции в классе Hδ при δ < 1»V. Kabaila. Dėl straipsnio „Kai kurie interpoliacijos uždaviniai Hδ klasėje, kai δ < 1“